Estudo integrado da espécie palmeira ouricuri (Syagrus coronata (Martius) Beccari) para geração de energia - Oliveira, Maria Beatriz Farias de (2013)
Fossil oil is the major source of energy and pre salt deposits were discovered recently. Besides that, this source is not renewable and one possible substitute is the energy from biomass. In this context, one of the biggest challenges is to develop energy matrices from alternative sources of low cost, making them economically competitive. Among the various alternatives, we highlight the use of biomass residues for energy generation by burning. This work aims to make the study of the species of palm native to northeastern Brazil, Syagrus coronate (Martius) Beccari as a potential use as an alternative energy source. When evaluating the quality of the parts of ouricuri, with and without compactation, for energy use and subsequent extraction and characterization of oil and biodiesel production is possible to observe a potential as an alternative energy source. Several parts of ouricuri samples presented to the calorific values around 17,000 J, and its calorific value is compared to biomass such as sugarcane bagasse and corn stover (which are widely used in the state of Alagoas).The biodiesel ethylic and methylic produced,from the oil of Ouricuri, in the presence of basic catalyst, are according to National Agency of Petroleum, Natural Gas and Biofuels specifications, considering the results of viscosity at 40 ºC, density to 20ºC, residue carbon, calorific power and cold filter plugging point.